Teaching Hospitals and the Disconnect Between Technology Adoption and Comparative Effectiveness Research: The Case of the Surgical Robot. (June 2017) - Makarov, Danil V.; Li, Huilin; Lepor, Herbert; Gross, Cary P.; Blustein, Jan
The surgical robot, a costly technology for treatment of prostate cancer with equivocal marginal benefit, rapidly diffused into clinical practice. We sought to evaluate the role of teaching in the early adoption phase of the surgical robot. Teaching hospitals were the primary early adopters: data from the Healthcare Cost and Utilization Project showed that surgical robots were acquired by 45.5% of major teaching, 18.0% of minor teaching and 8.0% of non-teaching hospitals during the early adoption phase. However, teaching hospital faculty produced little comparative effectiveness research: By 2008, only 24 published studies compared robotic prostatectomy outcomes to those of conventional techniques. Just ten of these studies (41.7%) were more than minimally powered, and only six (25%) involved cross-institutional collaborations. In adopting the surgical robot, teaching hospitals fulfilled their mission to innovate, but failed to generate corresponding scientific evidence.